Should Improvisation Be Regularly Included in Music Lessons? A Single-Case Quasi-Experimental Study Exploring the Differences in the Electrical Activity of the Brain between Musical Improvisation and Sight-Reading - Daniel Mateos-Moreno; Ernst Erlanson (MDPI AG, 2023)
Thanks to advances in portable electroencephalography technology (PEEGT), investigating the states of the mind is a relatively new area of research with a promising future in music education. Our aim, drawing upon PEEGT, was to contribute to the study of the differences in brain activity between piano music improvisation and sight-reading. We used the EMOTIV Insight helmet to register brain activity in repeated instances of one purposefully selected case while pursuing these two activities in experimental, controlled conditions. Thereafter, we pursued descriptive and robust statistical analysis of the variables offered by the Emotiv software. The quantitative data resulting from our study were triangulated with the qualitative analysis of a logbook filled by the participant on his subjective experiences. While the quantitative results were not statistically significant in measuring differences between the experimental conditions, trends were indeed found in the data and triangulated by our qualitative results. Our study provides preliminary evidence that supports the value of regularly incorporating musical improvisation moments in music education. This, to increase the students' excitement towards music lessons in cases that are similar to the case under scrutiny. Finally, implications and limitations are discussed in relation to the research design, the use of PEEGT technology, and the Emotiv software and hardware for investigating brain activity in pursuing musical activities.